(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
This research was conducted at the farm of the Universidad de los Llanos, Villavicencio Meta, in order to determine the nutritional quality and potential use in animal feeding: Salix humboldtiana willd, Erythrina rubrinervia and Maytenus laxiflorus) used three crossed with Brown Swiss cows rumen fistulated. These animals were randomized Latin square design single overshift 3 x 3. The treatments consisted of providing daily as food suplemento three kilograms of dry matter of crushed leaves of three species adding molasses. The basal diet consisted of grass Pennisetum clandestinum haylage. In degradation test was used nylon bags of 20 x 10 cm with an average pore 40 microns. The bags were filled with 5 grams of ground dried leaves of each tree species and P. clandestinum haylage. Ruminal degradability was measured in situ on rumen dry matter (DMD) of neutral detergent fiber (NDFD) and total nitrogen (DNT) at 6, 12, 24, 48 and 72 hours. In rumen fluid pH measurements were made and the concentration of ammonia nitrogen (N- NH3) (mg/100 ml) at 0, 4, 8 and 12 hours. The foliage M. laxiflorus presented a higher DMD and NDFD (P<0.05), followed by S. Humboldt, the lowest being those of E. rubrinervia (P<0.05). The three tree species had DMD, NDFD and DNT higher than those found in P. clandestinum haylage. S. humboldtiana DNT presented numerically one higher (84.38%) after 72 hours of incubation in relation to the other two treatments. The ruminal pH at different times was always slightly basic being at 0 hours, when moved closer to neutrality. The N-NH3 concentration (mg/100 ml) ensure a favorable environment bacterial flora in rumen, and The N-NH3 concentration increased after food intake at 4 h with a greater concentration (P<0.05), in the treatment E. rubrinervia (18.67 ml/100 ml rumen fluid), while their degradation rates (% material/hour) of DM and NDF were lower (P<0.05). NT degradation rate was lower for M. laxiflorus (P<0.05). That the three trees in the study had good responses in most of the variables studied, being better the behavior of M. laxiflorus regarding NDFD the DMS and, therefore, these three species have great potential fodder for use in ruminant feed.